The Public's Role in Seismic Design Provisions. Issue 3 (August 2016) - Davis, Michael; Porter, Keith
Seismic design provisions in the United States reflect structural engineers' experience, technical capabilities, and judgment of what is in the public's interest. Yet the American Society of Civil Engineers' (ASCE) Code of Ethics implicitly requires civil engineers to make a reasonable effort to elicit and reflect the preferences of the public, whose lives and livelihoods are at stake, when setting performance objectives. The public seems capable of expressing its preferences clearly, as suggested by the San Francisco Community Action Plan for Seismic Safety and the residential code enhancement adopted by Moore, Oklahoma. And at least one public opinion survey suggests that people in earthquake country prefer better performance than the code intends for new buildings, namely, that buildings should largely remain functional or habitable after a large earthquake. The public also seems willing to pay more for new buildings that meet its expectations.